ZnFe2O4-TiO2 Nanoparticles within Mesoporous MCM-41. (31st July 2012) - Tang, Aidong; Deng, Yuehua; Jin, Jiao; Yang, Huaming
Abstract : A novel nanocomposite ZnFe2 O4 -TiO2 /MCM-41 (ZTM) was synthesized by a sol-gel method and characterized through X-ray diffraction (XRD), high-resolution transmission electron microscopy (HRTEM), N2 adsorption-desorption, Raman spectroscopy, and ultraviolet visible (UV-vis) spectrophotometry. The results confirmed the incorporation of ZnFe2 O4 -TiO2 nanoparticles inside the pores of the mesoporous MCM-41 host without destroying its integrity. ZnFe2 O4 nanoparticles can inhibit the transformation of anatase into rutile phase of TiO2 . Incorporation of ZnFe2 O4 -TiO2 within MCM-41 avoided the agglomeration of nanoparticles and reduced the band gap energy of TiO2 to enhance its visible light photocatalytic activity. UV-vis absorption edges of ZTM nanocomposites redshifted with the increase of Zn/Ti molar ratio. The nanocomposite approach could be a potential choice for enhancing the photoactivity of TiO2, indicating an interesting application in the photodegradation and photoelectric fields.